CLINICAL CHARACTERISTICS IN PATIENTS WITH INFECTIOUS MONONUCLEOSIS - Keldiyorova Z. D. (Galaxy International Interdisciplinary Research Journal, 2023)
To conduct this study and obtain reliable results, it is necessary to select a certain number of studies, the object of study and the subject, in addition, for statistical analysis, the number of observations (n) should be sufficient. For this reason, we considered it appropriate to dwell on the research materials in more detail.